2016
DOI: 10.4049/jimmunol.1601134
|View full text |Cite
|
Sign up to set email alerts
|

An HIV-1 Env–Antibody Complex Focuses Antibody Responses to Conserved Neutralizing Epitopes

Abstract: Elicitation of broadly neutralizing antibody (bNAb) responses to the conserved elements of the HIV-1 envelope glycoproteins (Env), including the primary receptor CD4 binding site (CD4bs), is a major focus of vaccine development yet to be accomplished. However, a large number of CD4bs-directed bNAbs have been isolated from HIV-1 infected individuals. Comparison of the the routes of binding used by the CD4bs-directed bNAbs from patients and the vaccine-elicited CD4bs-directed monoclonal antibodies (MAbs) indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 66 publications
0
25
0
Order By: Relevance
“…Immune complex vaccines have been studied for many years preclinically 28 and have also entered clinical trials 31,32,48 . In the setting of HIV vaccines, complexation with mAbs has been used to alter the accessibility of neutralizing vs. non-neutralizing epitopes or alter conformations of the immunogen, promoting B cell responses against neutralizing epitopes 28 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Immune complex vaccines have been studied for many years preclinically 28 and have also entered clinical trials 31,32,48 . In the setting of HIV vaccines, complexation with mAbs has been used to alter the accessibility of neutralizing vs. non-neutralizing epitopes or alter conformations of the immunogen, promoting B cell responses against neutralizing epitopes 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Immune complex vaccines have been studied for many years preclinically 28 and have also entered clinical trials 31,32,48 . In the setting of HIV vaccines, complexation with mAbs has been used to alter the accessibility of neutralizing vs. non-neutralizing epitopes or alter conformations of the immunogen, promoting B cell responses against neutralizing epitopes 28 . Motivated by the recent findings that the base of Env trimers is a highly immunodominant non-neutralizing target on SOSIP immunogens 46,49,50 , we utilized a mAb isolated from macaques recognizing a base epitope for IC formation, with the goal of masking humoral responses against the base.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies revealed the specificities of neutralizing antibody responses in Env-vaccinated animals by isolating MAbs that recapitulate the plasma neutralizing capacity. The determined neutralizing specificities are mostly restricted to tier 1 viruses (10,(15)(16)(17)(18) or autologous tier 2 viruses (12,19,20). Thus, characterization of vaccine-elicited tier 2 virus NAb responses at a clonal level would provide an improved understanding of Env-specific Ab repertoires induced by vaccination, which is more relevant for future translational vaccine studies, in contrast to the characterization of infection-induced bNAbs pursued extensively in previous studies.…”
mentioning
confidence: 99%